Peran Kepemimpinan Dalam Pengembangan Mutu Pendidikan Islam (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
In our contemporary day, it appears to be getting harder to expand Islamic educational institutions in Indonesia. The management model needs to be updated and made more relevant in order to compete with other public institutions. As a result, the subject of raising educational standards must be taken seriously by all parties involved. This has a lot to do with leadership and management in educational institutions. Additionally, in order to raise educational standards, consideration must be given to all facets of the school, including inputs, processes, and outputs. The quality of education is viewed as crucial for development and change in all departments, especially leadership and management departments. Success in education depends on efficient management, which calls for effective leadership. Organization, direction, and supervision, as well as constant evaluation and monitoring for future actions, are all managerial responsibilities of a leader.